O gestor de cooperativa de crédito e a influência do seu comportamento estratégico na participação orçamentária, assimetria informacional e folga orçamentária - Lorenzini, Lucas Precoma (2021)
This research aimed to analyze the influence of the strategic behavior of credit union managers, with budgetary participation, information asymmetry and budgetary slack. It is noteworthy that the knowledge of the relationships of budget variables is vast, especially with regard to budgetary participation, informational asymmetry and budgetary slack, however, the influence of the individual's strategic behavior on these variables is a field to be explored. It is also highlighted that cooperativism is a fertile ground for research, credit unions lack their own solutions and often use the knowledge generated for publicly traded companies, seeking assertiveness in their processes, which justifies this focus for the elaboration of this study. Based on studies on the subject, it was expected that the average of all strategic behavior groups would be different in relation to budgetary participation (H1), to be different in relation to informational asymmetry (H2), to be different in relation to budgetary slack ( H3). In order to achieve the proposed objectives and test the hypotheses, the research is characterized as descriptive, survey and quantitative, with data from sixty-one (61) credit cooperative managers in the state of Paraná. First, the respondents were classified according to their strategic typology based on the studies by Miles and Snow (1978) and Conant, Mokwa and Varadarajan (1990), using the statistical tool Multivariate Analysis of Variance (MANOVA) as an analysis procedure in order to confirm or reject the raised hypotheses and in a way confirming the original classification of strategic behavior the Multiple Discriminant Analysis (MDA). The results suggest a difference of negative and significant average between the defending behavior and the other behaviors regarding budgetary participation, thus accepting hypothesis H1, a difference of negative and significant average between the analytical strategic behavior and the prospector and reactive behavior in the regarding informational asymmetry, thus accepting hypothesis H2, and finally no evidence of significant differences was found between strategic behaviors in relation to the budgetary slack variable, thus rejecting hypothesis H3. Multiple discriminant analysis (MDA) returned an assertiveness of 69% of the originally identified strategic behaviors. The implications of this research in the professional field enable better monitoring and selection of managers for certain areas of activity in the credit union and end up reinforcing the need for studies aimed at the cooperative sector, in addition to having explored the use of behavioral theories in the scope budget.